Healthy Workplaces? A Survey of Massachusetts Employers - Tremblay, Patricia A. (Am J Health Promot, 2013)
PURPOSE: This study examines worksite health promotion (WHP) and occupational health and safety (OHS) activities by Massachusetts employers, and the extent to which workplaces with programming in one domain were more likely to have the other as well. DESIGN: In 2008, the Massachusetts Department of Public Health surveyed a stratified sample of Massachusetts worksites. SETTING: A mailed questionnaire to be completed by workplace representatives. SUBJECTS: Massachusetts worksites returning the questionnaire. MEASURES: Questionnaire items about worksite characteristics, WHP, and some OHS practices. ANALYSIS: We scored levels of WHP and OHS activity; examined the relationship between activities in the two domains by employer characteristics; and assessed self-reported coordination between them. RESULTS: The 890 responding worksites had higher scores for OHS (mean = 48% of practices, SD = 24%) than WHP (mean = 20%, SD = 12%). The difference between these scores varied by a factor of two across industry sectors and was smallest for workforces of 100+ employees (p = .001). Employers with no unionized workers reported fewer activities in both domains (p < .0001). Only 28% of respondents reported always/often coordinating OHS and WHP efforts; these organizations had more activities overall in both domains. CONCLUSION: Larger and unionized workplaces in Massachusetts were more likely to offer both WHP and OHS programming. Self-reported coordination was somewhat associated with more activity in both domains, although levels of WHP activity varied widely.